Obecność i rola audiodeskrypcji jako wizerunku audialnego, mediującego w akcie komunikacyjnym: badanie pilotażowe - Mikołajczyk, Kamila; Puppel, Joanna (Scripta Neophilologica Posnaniensia, 2020)
Audiodescription is a type of translation in which visual elements are transferred into verbal descriptions. Numerous studies discuss the influence of this additional narration on media accessibility for its target audiences, namely partially sighted and blind people. Nevertheless, the impact of audiodescription on different audiences, such as sighted people, is still underdeveloped. The aim of this article is to investigate the influence of audiodescription which can be considered an example of mediation in the act of communication, on sighted audiences.